Effectiveness of Matching Game on Adolescent Girls' Menarche Knowledge Level - Readytia, Eilena Prudencia; Umaroh, Umaroh; Amartha, Tecky Afifah Santy (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Menarche marks the beginning of puberty for girls and requires adequate knowledge for proper preparation. A preliminary study revealed that all 11 students had misconceptions about menarche, highlighting the need for effective health education. This research evaluates the effectiveness of a matching game in increasing menarche knowledge among female adolescents at SD Kristen 03 Salatiga using a quasi-experimental design with a two-group pre-test post-test control group, where the control group received a leaflet. The sample included 42 participants from classes V and VI, with data collected by questionnaire and analyzed using univariate and bivariate analyses, specifically Wilcoxon statistical tests (p<0.05) and independent t-tests. The majority of respondents were 11 years old (76.2%) and 12 years old (23.8%). Menarche knowledge scores significantly increased from 62.86 to 94.05 after the matching game intervention and from 63.33 to 93.81 after the leaflet control group, both with p-values of 0.000, indicating that both interventions effectively improved knowledge. Mathematically, the score increase in the matching game group was 0.71 points higher than in the leaflet group. Although not statistically significant (p = 0.731), the 2.33% higher effectiveness of the matching game suggests its potential as a more engaging educational tool. This study demonstrates the effectiveness of matching games in adolescent reproductive health education and suggests future research to develop digital matching games to increase engagement.